Pripovedništvo praznine - Vogrinčič, Ana (Primerjalna književnost, 2003)
Blank Fiction. The Obsessive Consumerism of American Psycho. Within a wider treatment of a segment of contemporary American fiction, known as blank fiction, the paper centers on one of its most representative novels, American Psycho by Brett Easton Ellis (1991), and examines its manifestations of consumerism, apparent mostly on the level of the narrative, which puts the main hero in a role of the absolute consumer in content and in form. Referring to the examples of Ellis's specific narrative devices which reduce the main character to a mere rhetorical instrument a thesis is developed that points to the total constructedness and, consequently utter impossibility of even only fictional existence of the central figure.
Keywords: Ellis, Brett Easton; pripovedništvo; potrošništvo; pripovedništvo praznine; American literature; ameriška književnost